Protecting Jerusalem's holy sites : a strategy for negotiating a sacred peace - Guinn, David E. (Cambridge University Press, 2006)
The holy sites in Jerusalem exist as objects of international veneration and sites of nationalist contest. They stand at the heart of the Israeli-Palestinian conflict, yet surprisingly, the many efforts to promote peace, mostly by those outside the Middle East, have ignored the problem. This book seeks to address this omission by focusing upon proposals of development of a legal regime to protect the holy sites separable from the final peace negotiations to not only protect the holy sites but promote peace by removing these particularly volatile icons from the field of conflict. Peace and the protection of the holy sites cannot occur without the consent and cooperation of those on the ground. This book supports local involvement by developing a comprehensive plan for how to negotiate: outlining the relevant history, highlighting issues of import, and identifying effective strategies for promoting negotiation. -- Publisher description.